2019
DOI: 10.1063/1.5102142
|View full text |Cite
|
Sign up to set email alerts
|

Glass transition of LiCl aqueous solutions confined in mesoporous silica

Abstract: The thermal transitions of confined LiCl aqueous solutions were studied by differential scanning calorimetry for solutions with salt concentrations with eutectic (R = 7) and subeutectic (R > 7) compositions (R = moles of water/moles of LiCl). The confinement media consist of mesoporous silica with pore diameters between 2 nm and 58 nm, with a small negative surface charge density. The vitrification of confined LiCl aqueous solutions was observed in all samples, expanding the vitrification region up to R = 15, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…As a reference, LiCl solutions vitrify at a deeper supercooled state and experience almost negligible changes in T g when confined in nanopores (Fig. 2(f)), as reported by Corti et al [19] However, for LiFSI solutions in zones I and II, confinement significantly decreases T g at LiFSI•4.5H 2 O. This effect gradually weakens as water content increases and ultimately disappears at LiFSI•13H 2 O (see Fig.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…As a reference, LiCl solutions vitrify at a deeper supercooled state and experience almost negligible changes in T g when confined in nanopores (Fig. 2(f)), as reported by Corti et al [19] However, for LiFSI solutions in zones I and II, confinement significantly decreases T g at LiFSI•4.5H 2 O. This effect gradually weakens as water content increases and ultimately disappears at LiFSI•13H 2 O (see Fig.…”
Section: Resultssupporting
confidence: 75%
“…One objective is to understand the structural and dynamic inhomogeneity in deeply supercooled glass-forming liquids. [13][14][15][16][17][18][19][20][21][22][23][24][25] It is reasonable to propose that the size of the spatial constraint should be the upper limit of the heterogeneous domains of glass forming liquids. [23,26] Hence, when it comes to confinement, it is expected that nanometer-sized pores or channels, especially with diameters less than 2 nm, will reduce the glass transition temperature T g of confined liquids, as compared to the T g of bulk liquids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with these studies at room temperature, it was found in calorimetric measurements at cryogenic temperatures that the glass transition temperature Tg is only slightly higher in such narrow silica confinements. 20 Electrolyte solutions are also interesting from a different perspective, namely, for improving our understanding of the various anomalies of water. Most researchers agree that the water anomalies originate in the supercooled liquid regime.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Against this backdrop, it is intriguing to ascertain confinement effects for water-mimetic liquids, in particular, for LiCl solutions. While the aforementioned studies addressed this problem at high or low temperatures, [17][18][19][20] it is the goal of this contribution to investigate the dynamics of glass-forming LiCl solutions in silica pores of various diameters d throughout the whole supercooled temperature range, especially near the proposed second critical point of bulk water at ∼225 K.…”
Section: Introductionmentioning
confidence: 99%